Impact of the integrated development management (IDM) approach on the delivery of water, sanitation and hygiene (WASH) services in Binga district - Nyamuranga, Stewart Tongesayi (Midlands State University, 2017)
An integrated approach continues to be recognized as the most prudent path to sustainable development. The assumption is that any successful development must take into account the economic, social, cultural, environmental and geographic realities that shape the lives of people. The study therefore sought to examine the impact of the integrated development management approach on the delivery of WASH services to the rural poor. The study used a case study design by focusing on Binga district of Matabeleland North province. The research adopted a mixed research method with primary data having being collected from three (3) wards. 100 respondents were sampled out of which research instruments in the form of questionnaires, interviews and focus group discussions were administered. Results from the study show that, although application of the integrated approach is theoretically noble, its adoption and application to the WASH sector has not yielded much positive impact on the delivery of WASH services to the rural poor. The integrated WASH structures at the various levels are riddled with challenges related to financing, inconsistent membership and representation, duplication of membership roles, ineffective coordination, inefficiencies in decision-making and undemocratic leadership. The study has recommended that central government and the Rural District Council should increase their level of funding to the NAC structures at all levels. The study further recommended that the main NAC embarks on a policy paradigm aimed at strengthening the WASH governance structures at all levels through redefining membership roles, streamlining membership and ensuring democratic leadership in all the structures. The NAC and its sub-structures was further recommended to embark on a major advocacy drive with both central and local government on increased funding.